Nauka o przedsiębiorstwie - między wiedzą teoretyczną a praktyczną - Sokołowska, Agnieszka (Enterprise Science - between Theoretical and Practical Knowledge, 2008)
Multidimensional relations between theoretical and practical knowledge are one of the problems concerning the development of enterprise science which - balancing between them - performs not only cognitive function (describes changeable reality), but also normative function (resulting) from practical character of effects of research on science in enterprise. The article focuses on connection between theoretical and practical knowledge in enterprise science, emphasizes enterprise theory and practice challenges, identifies relations between them, and indicates symptoms of the present phase of enterprise science development. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 29-39